2012
DOI: 10.5251/ajfn.2012.2.2.51.54
|View full text |Cite
|
Sign up to set email alerts
|

Proton – induced X – Ray emission (Pixe) Analysis of some sea food from Western Niger Delta, Nigeria

Abstract: Periwinkles and crayfish are among the sea foods widely consumed by the people living in the coastal region of Nigeria. The systematic determination of trace -element concentration in periwinkles and Cray fish samples was done by the PIXE method using a 3.0 MeV proton beam obtained from CERD (OAU, Ile-Ife) ion beam analysis (IBA) facility. The following elements where detected and measured in all the samples Na, Ca, Mg, S, CI, K, Si, Fe, Cu, Zn, Br, Sr, the concentration of the elements varied in the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In particular, the elemental content of K, Ca, Fe, Cu, Zn, As, Se, Sr were 95-108% relative to certified values for SRM Bovine Liver. Agaja and Obiajunwa [21] validated PIXE technique by analysing the SRM Bovine Liver (1577a) and observed 60-100% of recovery for the elements K, Ca, Mn, Fe, Cu, Zn, Br and Rb whereas in the study of Biswas et al [22], 90-110% of recovery was reported for the same elements. Campbell [23] reported that the elements Fe, Cu, Mn, Zn, Se, Br and Rb were within 91-127 % relative to certified values.…”
Section: Comparison Of Values Determined By Pixe With Certified Valuesmentioning
confidence: 98%
“…In particular, the elemental content of K, Ca, Fe, Cu, Zn, As, Se, Sr were 95-108% relative to certified values for SRM Bovine Liver. Agaja and Obiajunwa [21] validated PIXE technique by analysing the SRM Bovine Liver (1577a) and observed 60-100% of recovery for the elements K, Ca, Mn, Fe, Cu, Zn, Br and Rb whereas in the study of Biswas et al [22], 90-110% of recovery was reported for the same elements. Campbell [23] reported that the elements Fe, Cu, Mn, Zn, Se, Br and Rb were within 91-127 % relative to certified values.…”
Section: Comparison Of Values Determined By Pixe With Certified Valuesmentioning
confidence: 98%